Effect of exogenous free Nε-(carboxymethyl)lysine on diabetes-associated cognitive dysfunction: neuroinflammation, and metabolic disorders - Huang Zhang; Lan Mo; Xi Chen; Mei Li; Maiquan Li; Yang Xu; Maomao Zeng; Zhiyong He; Qingwu Shen; Jie Chen; Wei Quan (Food Science and Human Wellness)
Diabetes-associated cognitive dysfunction has already been attracted considerable attention. Advanced glycation end products (AGEs) from daily diets are thought to be a vital contributor to the development of this diseases. However, the effect of one of the best-characterized exogenous AGEs Nε-(carboxymethyl)lysine (CML) on cognitive function is not fully reported. In the present study, diabetical Goto-Kakizaki (GK) rats were treated with free CML for 8-weeks. It was found that oral consumption of exogenous CML significantly aggravated diabetes-associated cognitive dysfunction in behavioral test. In details, exogenous CML increased levels of oxidative stress, promoted the activation of glial cells in the brain, up-regulated the release of inflammatory cytokines interleukin-6, inhibited the protein expression of the brain-derived neurotrophic factor and thus led to neuroinflammation. Furthermore, exogenous CML promoted the amyloidogenesis in the brain of GK rats, and inhibited the expression of GLUT4. Additionally, several tricarboxylic acid cycle and glutamate-glutamine/γ-aminobutyric acid cycle intermediates including pyruvate, succinic acid, glutamine, glutamate were significantly changed in brain of GK rats treated with exogenous free CML. In conclusion, exogenous free CML is a potentially noxious compounds led to aggravated diabetes-associated cognitive dysfunction which could be possibly explained by its effects on neuroinflammation, energy and neurotransmitter amino acid homeostasis.